MAJOR LYMPHOCYTE SUBPOPULATIONS IN COMBINED INFECTIONS HERPES VIRUS (HSV) AND VARIOUS FORMS OF TUBERCULOSIS - M. A. Karalyan (Медицинская иммунология)
The goal of present work was to study main cell subpopulations of immune system, frequency of human herpes virus (HSV) type 1 activation, and presence of HSV in patients with tuberculosis (TB). We have shown an increased level of herpesvirus type 1 and type 2 manifestation in patients with different types of tuberculosis (TB). A statistically significant decrease in the CD4/CD8 ratio and in percentage of CD3+, CD4+ cells patients with certain clinical forms of TB was shown, as compared to the group with active HSV infection. The data obtained showed absence of correlation between TB-related reactions, HSV infection, and levels of HSV-specific antibodies. Deficient function of cells with natural killer (NK) activity, and decreased numbers of CD56+ cells have been also of shown. NK cells may be among most relevant components of immune reactions to HSV infection. Main role in HSV activation in the TB patients depends on deficiency of NK-like cells.